Nursing interventions to help prevent children from working on the streets - KADIOĞLU, HASİBE (WILEY-BLACKWELL, 2016)
Aim: The purpose of this study was to assess the impact of a programme developed by the researchers entitled, 'The Streets are Not the Solution' for preventing children from working on the streets. Background: To date, public health nursing interventions preventing child labour have been limited. Public health nursing interventions occupy an important place in preventing children from working on the street. Methods: This was an semi-experimental study conducted over the period April 2011-July 2012. Thirty-six children working on the streets and their mothers were recruited in Izmit, Turkey. As part of the programme, the subjects took part in nine educational sessions, received individual consulting services, and the mothers attended a jewellery-making course. The impact of the programme was evaluated three times, once before the activity, then at the end of the activity, and later, three months after the programme was over. The Family Evaluation Form, The Child/Parental Acceptance-Rejection-Control Questionnaire, the Multidimensional Scale of Perceived Social Support and the Problem Solving Inventory were used as data collection tools. Informed consent was obtained from the participants. Results: This programme was effective in helping mothers to develop their parental roles, increasing the mothers' network of social support, developing their problem-solving skills and preventing their children from working on the streets. Discussion: To prevent children from working on the streets includes family based applications such as public health nursing interventions. Conclusion and implications for nursing and health policy: The roles of public health nurses about preventing children from working on the streets must be adopted in the healthcare system.
Keywords: Child Protection; Poverty; Public Health Nursing; Nursing Roles; ACCEPTANCE